Proceedings of the International Meeting AI-Pocalypse: How AI is turning academia upside down – May 28th - Ramos, M.; Louçã, Jorge (2025)
The bots aren’t just coming, they’ve already set up camp in the ivory tower, grading essays, drafting abstracts, writing papers, and even applying for grants. From student essays so baffling they’d make Shakespeare question his career choices to algorithms “predicting” Nobel Prize winners before they’ve mastered diaper changes, academia has a new lab partner, and it’s really good at crib notes. Lecture halls will move to server rooms. Will AI catapult us into a golden age of discovery, or just flood inboxes with extremely polite academic spam? Peer-reviewed journals may sink under AI-generated feedback loops, and tenure-track bots could soon demand sabbaticals in the cloud. Join us for a lively debate on whether your next research partner will be a human or a glorified “humanized” autocorrect that thinks adding “quantum” to any sentence makes it sound smarter. We’ll tackle burning questions: When will libraries become bot-generated fanfiction archives? How much will AI students pay in tuition? What’s the protocol if a bot wins a Nobel?